Monitoring of Communication Precursors in Extremely Low Birth Weight (ELBW) Newborns by Video Analysis Method: Preliminary Results - Laura Sundas; Silvia Palma; Marisa Pugliese; Maria Federica Roversi; Enrico Apa; Alberto Berardi; Elisabetta Genovese; Daniele Monzani (MDPI AG, 2022)
Background: The survival of extremely low birth weight infants (ELBW) has increased worldwide. Even in the absence of major disabilities, ELBW infants show difficulty in simple language functions. It is relevant to assess early abilities, which are the base of early linguistic skills, in order to implement customized intervention programs in ELBW infants. Aims: To evaluate communication precursors of language development in ELBW infants at 12 and 24 months of correct age (C.A). To investigate the correlation of linguistic and communicative prerequisites with mental development outcome at 24 months CA. Method: 52 ELBW neonates (mean gestational age 26.6 weeks, mean birth weight was 775 g) who were admitted to the neonatal intensive care unit of the University Hospital of Modena, were enrolled. Data were collected from archived audio-video recordings of neurodevelopmental follow-up visits. Video analysis of communicative and linguistic developmental was performed at 12 and 24 months CA. Neurodevelopmental outcome was evaluated with Mental Developmental Scales (GMDS-R). Results: The video-analysis showed that infants at 12 months CA used predominantly eye contacts and gestural turns, while vocal turns were scant. At 24 months CA, a significant change in eye contacts, vocal turns, gestural turns, and utterances (p < 0.001) occurred. The total number of utterances (p = 0.036) and eye contacts (p = 0.045) were significantly correlated to the Development Quotient (DQ) of Hearing and Language scale. Moreover, a significant correlation was found with the Personal-Social scale vocal turns (p = 0.009) and the total number of utterances (p = 0,02). Finally, the Global Quotient of the GMDS-R was related to the Vocal Turns (p = 0.034) and the total number of Utterances (p = 0.013). Conclusions: ELBW infants at 12 months CA use predominantly eye contacts and gestural turns to communicate with adults. At 24 months CA, the child's communicative intention evolves from gestural to verbal communication. The latter is characterized by an increase in both vocal turns and the number of utterances produced during interaction. The video analysis we implement appears to be a sensitive tool for early assessment of communication and language development and to refine early intervention